MODERN ACQUISITIONS OF THE UZBEK LANGUAGE, WHICH HAVE ENTERED THE SPHERE OF EDUCATION FROM RUSSIAN AND ENGLISH LANGUAGES - Mustafokulova Zarifa Bakhodir kizi (Лучшие интеллектуальные исследования, 2024)
Abstract: This article examines in detail that have entered our language today and are actively used in speech, as well as comments on their classification, their replacement by the Uzbek alternative. The article analyzes the meaning of neologisms that have entered our language. It is stated that these neologisms come mainly from the English language, and the types of these neologisms are given.